Back to school with asthma in 2021. (2nd September 2021) - Henry, Heather
Abstract : September is a peak time for asthma exacerbations in school-aged children. Heather Henry looks at the role of the general practice nurse in reducing this risk Each September marks a peak in asthma exacerbations in children returning to school for the autumn term. Children and families face the challenges of disturbed asthma management regimes, seasonal infections and asthma triggers. This year presents an additional challenge, coming as it does during a global pandemic, with primary care at breaking point. This article presents a pragmatic approach to prioritising the most at-risk children.